1999
DOI: 10.1002/etc.5620180313
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organochlorine contaminants among sea otter (Enhydra lutris) populations in California and Alaska

Abstract: Abstract-Organochlorine pesticides, polychlorinated biphenyls (PCBs) including non-ortho PCBs, polychlorinated dibenzo-pdioxins (PCDDs), and polychlorinated dibenzofurans (PCDFs) were measured in sea otter liver tissue from California, southeast Alaska, and the western Aleutian archipelago collected between 1988 and 1992. Average total dichlorodiphenyltrichloroethane concentrations for California otters (850 g/kg wet weight) were over 20 times higher than in Aleutian otters (40 g/kg) and over 800 times higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Both TCPME and TCPMOH were detected in several prey species of sea otters. An earlier study has reported the occurrence of 4 ng TCPMOH/g liver in sea otters [17]. Lipid‐normalized concentrations of TCPMOH in sea otter livers (100 ng/g) were approximately ninefold greater than concentrations found in prey items (11 ng/g), suggesting biomagnification of this compound in the sea otter food chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both TCPME and TCPMOH were detected in several prey species of sea otters. An earlier study has reported the occurrence of 4 ng TCPMOH/g liver in sea otters [17]. Lipid‐normalized concentrations of TCPMOH in sea otter livers (100 ng/g) were approximately ninefold greater than concentrations found in prey items (11 ng/g), suggesting biomagnification of this compound in the sea otter food chain.…”
Section: Resultsmentioning
confidence: 99%
“…The estimates of TEQs in sea otters and shellfish prey may be considered conservative, because they only represent a few mono‐ and non‐ ortho congeners and do not consider di‐ ortho PCBs, which are present at considerable concentrations in sea otters. In addition, other dioxin‐like compounds, such as polychlorinated dibenzo‐ p ‐dioxins and dibenzofurans [17], may add to the existing burdens of TEQs in sea otters and their prey. Furthermore, mammalian TEFs were derived based on studies with terrestrial mammals.…”
Section: Resultsmentioning
confidence: 99%
“…Many environmental contaminants, including heavy metals and organochlorines, are associated with industrial emissions and large-scale agriculture, yet studies have demonstrated elevated levels of some contaminants far from known or suspected sources (Bacon et al, 1999;Bard, 1999). Top-level predators, such as bald eagles (Haliaeetus leucocephalus), are believed to be especially vulnerable to many contaminants and can be used as sentinel species for contaminated areas (Welch, 1994;Holl and Cairns, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent use of DDT in China and southeast Asia compared with North America [55] and evidence for trans‐ Pacific transportation of DDT [48], Laysan albatross do not show elevated concentrations of DDT‐related compounds, including TCPMe, compared with blackfooted albatross. The DDT contamination of marine food webs along the west coast of North America remains relatively high [47,56] and, although data for comparable species are limited, is higher than in marine food webs from the Asian coast of the Pacific [2,57]. The TCPMe/OH concentrations also appear to be greater in North American waters than in Asia [57,58].…”
Section: Discussionmentioning
confidence: 99%